Planning to cope with tropical and subtropical climate change - Tiepolo, Maurizio; Ponte, Enrico; Cristofori, Elena; Barabach, Jan; Bongard, Cindy (De Gruyter Open, 2016)
Subtropical and tropical medium-large size cities are rarely provided with climate plans. Too often these plans are of low quality. This book provides examples to increase the quality of climate planning through climate change caracterization, risk analysis and evaluation, adaptation mainstreaming and vulnerability identification